2018
DOI: 10.1039/c7ra13242e
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and optoelectronic properties of terthiophene- and bithiophene-based polybenzofulvene derivatives

Abstract: The electrochemical behavior of some polybenzofulvene derivatives bearing bithiophene (BT) or terthiophene (TT) side chains was investigated by cyclic voltammetry and cross-linked materials were obtained by dimerization of the BT or TT side chains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…In particular, interesting new drug delivery systems were developed through the insertion of oligoethylene glycol (OEG) side chain or the conjugation with biocompatible macromolecules [33,34,35,36,37,38,39,40]. Moreover, the structural manipulation of the 3-phenylindene moiety has provided intriguing results in the optoelectronic field, leading to potentially useful polymers in the fabrication of OLED devices [41,42,43,44,45,46,47,48]. However, these results were obtained after intensive structure-property relationship studies were performed on monomer BF1 and focused on the identification of the effects of different substituents on the polymer properties (i.e., spontaneous polymerization, molecular weight distribution, structure, thermoreversibility, photophysical features, and aggregation).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, interesting new drug delivery systems were developed through the insertion of oligoethylene glycol (OEG) side chain or the conjugation with biocompatible macromolecules [33,34,35,36,37,38,39,40]. Moreover, the structural manipulation of the 3-phenylindene moiety has provided intriguing results in the optoelectronic field, leading to potentially useful polymers in the fabrication of OLED devices [41,42,43,44,45,46,47,48]. However, these results were obtained after intensive structure-property relationship studies were performed on monomer BF1 and focused on the identification of the effects of different substituents on the polymer properties (i.e., spontaneous polymerization, molecular weight distribution, structure, thermoreversibility, photophysical features, and aggregation).…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, 1 features an extended conjugation due to a 3phenylindene-2-carboxylate scaffold, the structure at the basis of the polybenzofulvene monomeric unit (Figure 1C). [52][53][54][55][56][57][58][59][60][61][62][63][64][65] We also show that the obtained LDMS 1 can be easily functionalized with a clickable azide group (compound 2) for the insertion of the photoswitch in more complex synthetic and/or biological structures via azide-alkyne click reactions. In fact, we report that methyl-end-capped nona(ethylene glycol) (NEG) side chain, an amphiphilic solubilizing group, [66] can be successfully conjugated with 2 in a preliminary effort to obtain an amphiphilic LDMS capable of self-assembling in nanometric micelles in water solution and operated by visible light (Figure 1D).…”
Section: Introductionmentioning
confidence: 70%
“…In general, PPBFB derivatives are amphiphilic macromolecules capable of interacting with a wide range of solvents. In particular, previously published poly-6-MOEG-9-TM- BF3k (obtained by means of the “grafting through” or “grafting onto” approaches) showed an excellent solubility in the most common organic solvents [22,23]. Its dissolution in dichloromethane or chloroform is very rapid, while the interaction with water is slower, but it led, however, to transparent solutions.…”
Section: Resultsmentioning
confidence: 99%
“…The characterization studies suggested, for this hydrophobic polybenzofulvene derivative, a vinyl structure stabilized by aromatic stacking interactions [9,10]. This intriguing finding led us to explore the chemistry of benzofulvene derivatives [11,12,13,14,15], and to prepare intriguing materials with potential applications in the optoelectronic field [16,17,18,19,20,21,22,23] and pharmaceutical science [24].…”
Section: Introductionmentioning
confidence: 99%